Recent Advances in the Synthesis of Enantiomerically Enriched Diaryl, Aryl Heteroaryl, and Diheteroaryl Alcohols through Addition of Organometallic Reagents to Carbonyl Compounds - Teixeira, Wystan K. O.; de Albuquerque, Danilo Yano; Narayanaperumal, Senthil; Schwab, Ricardo S. (Synthesis, 2020)
Enantiomerically enriched diaryl, aryl heteroaryl, and diheteroaryl alcohols are an important family of compounds known for their biological properties. Moreover, these molecules are highly privileged scaffolds used as building blocks for the synthesis of pharmaceutically relevant products. This short review provides background on the enantioselective arylation and heteroarylation of carbonyl compounds, as well as, the most significant improvements in this field with special emphasis on the application of organometallic reagents.1 Introduction2 Background on the Enantioselective Synthesis of Diaryl, Aryl Heteroaryl, and Diheteroaryl Alcohols3 Organozinc Reagents4 Organolithium Reagents5 Grignard Reagents6 Organoaluminum Reagents7 Organotitanium Reagents8 Organobismuth Reagents9 Miscellaneous10 Conclusion
Keywords: chiral alcohols; organometallic reagents; asymmetric addition; enantioselective arylation; heteroarylation